Fuentes de alimentación de la lombriz roja california (Eusenia foétida) en la producción de humus, Mocache 2014. - Sinchiguano Briones, Luís Ángel (2015)
This study was conducted at the Experimental Farm "La Maria" to 74 meters in cantón Mocache province of the Rivers. In order to evaluate four power supplies of the Californian red worm (Eusenia foétida) research was proposed. For this study design was applied in complete random (DBCA) blocks with eight repetitions. The variables evaluated were: Time projection (d), Performance (Kg) Chemical composition of humus (N, P y K), growth and increased earthworm population and establish the profitability of the treatments. As a result it was found that the less time it had split the household vegetable waste with 22.75 days; the best performance was for coconut raquis 40.37 Kg / m2; Within the chemical composition of humus produced into major banana rachis had a higher concentration of N, P and K, with 1.2, 0.50, and 1.58% respectively. Regarding the growth of household waste plant had the highest growth with 5.83cm; as the increase in plant population domiciliary Waste 1665 showed an increase of worms. The higher return was to raquis banana with a ratio benefit – cost of 1.18%.